Regulatory and legal status of clinical guidelines and their role in the quality control of medical care in countries of the European Union, North America and Asia - V. K. Fedyaeva; U. N. Dmitrieva; N. I. Juravleva; N. I. Juravlev; M. Yu. Kovaleva; A. S. Korobkina; O. A. Sukhorukikh; A. A. Pashkina (IRBIS LLC, 2019)
Introduction. In 2016-2018, the approaches to the development and use of clinical guidelines in the Russian Federation underwent substantial changes. As part of this work, legal aspects of clinical guidelines were modified. The present review, conducted on behalf of the Ministry of Health, is aimed to analyze the international experience regarding the clinical guidelines standards and identify possible obstacles and risks for their implementation.Materials and methods. We reviewed documents and publications related to the development and implementation of clinical guidelines in 2016-2017 in 12 countries from Europe, Asia and North America known for their well established health care systems. The search for publications has been conducted with the help of the PubMed bibliographic database and the Google search engine, using the following requests: «clinical practice guidelines legal status», «clinical practice guidelines + name of the country». The results were updated to 2019.Results. In most of the 12 countries, the clinical guideline development process is coordinated at the national level. However, the implementation of these guidelines by medical professionals is not mandatory, although it is often supported by the regulations of the national health system.Conclusion. The development and implementation of clinical guidelines in the Russian Federation is consistent with the international experience: the development of clinical guidelines is coordinated at the federal level in agreement with the principles of evidence-based medicine; the implementation of guidelines are not mandatory, however, medical organizations and health professionals are expected to provide the medical care by considering the clinical guidelines, approved by the Scientific and Practical Council of the Ministry of Health.